2017
DOI: 10.1021/acsnano.6b05992
|View full text |Cite
|
Sign up to set email alerts
|

Nanoparticles Associate with Intrinsically Disordered RNA-Binding Proteins

Abstract: Nanoparticles are capable of penetrating cells, but little is known about the way they interact with intracellular proteome. Here we show that inorganic nanoparticles associate with low-complexity, intrinsically disordered proteins from HeLa cytosolic protein extracts in nondenaturing in vitro nanoparticle pull-down assays. Intrinsic protein disorder associates with structural mobility, suggesting that side-chain flexibility plays an important role in the driving of a protein to nanoparticle absorption. Disord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 71 publications
0
9
0
1
Order By: Relevance
“…Though not recognized until very recently, IDPs play also a relevant role in a wide variety of biological processes 21 and are also involved in different diseases 22 . As shown by Moreno et al 8 , in dilute solutions SCNPs and IDPs exhibit similar scaling laws and the presence of intramolecular compact and weakly deformable domains connected by very flexible segments; also, dynamical analogies like the similar influence of the internal friction have been reported 9,23 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Though not recognized until very recently, IDPs play also a relevant role in a wide variety of biological processes 21 and are also involved in different diseases 22 . As shown by Moreno et al 8 , in dilute solutions SCNPs and IDPs exhibit similar scaling laws and the presence of intramolecular compact and weakly deformable domains connected by very flexible segments; also, dynamical analogies like the similar influence of the internal friction have been reported 9,23 .…”
Section: Introductionmentioning
confidence: 99%
“…This internal compartmentalization, together with their softness and ultrasmall size, is a feature that could be of utmost interest for their applications in nanotechnology: Sensing capabilities, controlled drug delivery, and catalytic applications of SCNPs have been recently demonstrated. 11−20 Although not recognized until very recently, IDPs play also a relevant role in a wide variety of biological processes 21 and are also involved in different diseases. 22 As shown by Moreno et al, 8 in dilute solutions, SCNPs and IDPs exhibit similar scaling laws and the presence of intramolecular compact and weakly deformable domains connected by very flexible segments; also, dynamical analogies like the similar influence of the internal friction have been reported.…”
Section: ■ Introductionmentioning
confidence: 99%
“…RNA nanotechnology resembles the characteristic features of DNA-based architectures built via canonical base pairing, while providing structural flexibility, functional diversity, and thermal stability over DNA nanoparticles. , RNA commonly forms well-tailored, relatively stable, and complex three-dimensional structures by adopting such properties including canonical or noncanonical base pairing, base stacking, and secondary or tertiary structural motifs. This is typically found in many biological RNAs and found less often in DNAs.…”
Section: Introductionmentioning
confidence: 99%
“…the interaction of Ab with silica is electrostatically driven. Furthermore, it has been reported that proteins with large intrinsically disordered regions are enriched in nanoparticle-adsorbed proteomes (48) attributed to the flexibility endowed by intrinsically disordered regions. Ab oligomers have been shown to have similarly well-ordered b-sheet cores with intrinsically disordered termini (49).…”
Section: Anionic Nb Surface Enables High Affinity For Ab and Its Specificitymentioning
confidence: 99%